A clinical comparative study to evaluate the efficacy of intubating doses of atracurium and cisatracurium in patients undergoing general anesthesia - Priyanka Harle; Preeti Goyal; Gupta, Abhishek; Namrata Jain; Kothari, Dilip (Asian Journal of Medical Sciences, 2022)
Background: Skeletal muscle relaxation is integral part of general anesthesia. Non-depolarizing neuromuscular blocking drugs like cisatracurium are devoid of any signs of histamine release and can improve the quality of intubating conditions. Aims and Objectives: We decided to assess the efficacy of Cisatracurium when compared to atracurium in terms of intubating conditions and hemodynamic parameters in patients undergoing surgeries under general anesthesia. Materials and Methods: In this study, 80 patients in the age group of 20–65 years were randomly allocated into Group A received Atracuruium 0.5 mg/kg and Group B received Cisatracurium 0.15 mg/kg for intubation after administration of induction agent. Intuabating conditions were assessed by Cooper et al., score and hemodynamic parameters such as heart rate and blood pressure were recorded at 1, 3, 5, 10, 15, and 30 min of intubation. Any signs of histamine release were noted. Results: Demographic profile was comparable between the two groups. As per Cooper et al., score intubating conditions were excellent with Cisatracurium group as compared to the atracurium group which was statistically significant. Hemodynamic parameters during intubation and after intubation were comparable between two groups. No associated signs of histamine release were noted in either of the groups. Conclusion: From our clinical comparative study, we have observed that Cisatracurium 0.15 mg/kg provides better intubating conditions and stable hemodynamic profile with no signs of histamine release as compared to atracurium 0.5 mg/kg dose.